Motivational variables and correlation between healthy lifestyles of students in Physical Education - Carrón, Maria (2017)
In our work we will focus on correlation between variables of lifestyle related to health and motivation ones, using the theoretical psychological needs (BPN) and autonomous motivation, which contributed to an explanation of variance in healthy behaviors, such as physical activity and sport participation.